2003
DOI: 10.4319/lo.2003.48.2.0647
|View full text |Cite
|
Sign up to set email alerts
|

Urease activity in cultures and field populations of the toxic dinoflagellate Alexandrium

Abstract: Nitrogen availability is an important factor controlling phytoplankton abundance and species composition in marine waters. In addition to inorganic nitrogen, some phytoplankton species can use dissolved organic nitrogen sources such as urea for growth. Herein we demonstrate that axenic laboratory cultures of the toxic dinoflagellate, Alexandrium fundyense strain CB301A and A. catenella strain TN9A were able to grow on urea as a sole nitrogen source in the presence of nickel. This nickel dependence suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 41 publications
8
74
1
Order By: Relevance
“…Accordingly, Ni must be considered an important prerequisite for diatom growth (Syrett and Peplinska, 1988). Dyhrman and Anderson (2003) made similar observations with respect to Ni for some dinoflagellate species. Apart from this, Ni is also essential for microbiologically-induced calcite precipitation.…”
Section: Biological Effects and Influencesmentioning
confidence: 53%
See 1 more Smart Citation
“…Accordingly, Ni must be considered an important prerequisite for diatom growth (Syrett and Peplinska, 1988). Dyhrman and Anderson (2003) made similar observations with respect to Ni for some dinoflagellate species. Apart from this, Ni is also essential for microbiologically-induced calcite precipitation.…”
Section: Biological Effects and Influencesmentioning
confidence: 53%
“…However, interactions between trace metals, in which one element becomes toxic due to the limitation of another, have been observed. For example, Egleston and Morel (2008) reported that Ni became toxic due to the limitation of Zn, resulting in toxicity to diatoms. Bruland et al (1991) found that synergistic and antagonistic interactions between Cu and potential biolimiting metals, such as Fe, Mn, and Zn, might have large effects on the production of marine biota.…”
Section: Biological Effects and Influencesmentioning
confidence: 99%
“…There is some evidence that urease may be constitutively expressed in some cyanobacteria, dinoflagellates and diatoms (Collier et al 1999, Peers et al 2000, Fan et al 2003. Relatively high rates of urease activity have been previously reported for the dinoflagellates Alexandrium fundyense and A. catenella (Dyhrman & Anderson 2003), as well as for Prorocentrum minimum (Fan et al 2003). Fan et al (2003) found that urease content per cell was significantly higher for the dinoflagellate P. minimum than for the either the diatom Thalassiosira weissflogii or the pelagophyte Aureococcus anophagefferens; however, on a per cell volume basis, A. anophagefferens had the highest activity.…”
Section: Discussionmentioning
confidence: 83%
“…In phytoplankton that have urease, a basal level of urease activity is usually always detectable, but the level of activity varies with N source (Antia et al 1991, Collier et al 1999, Peers et al 2000, Dyhrman & Anderson 2003, Lomas 2004, Solomon & Glibert 2008, suggesting that urease activity is regulated by external or internal factors, as is urea uptake. However, the pattern of regulation may differ not only among but also within phytoplankton taxonomic groups (Fig.…”
Section: Regulation Of Urea Catabolismmentioning
confidence: 99%